Molecular mechanisms of unique therapeutic potential of CUDC-907 for MEF2D fusion-driven BCP-ALL - Qing Xue; Ming Zhang; Yixiao Mo; Bo Jiao; Xuan Liu; Minghao Jiang; Yu Zhou; Yun Tan; Huimin Li; Jianming Zhang; Qianqian Zhang; Yunqi Li; et al. (Signal Transduction and Targeted Therapy)
Abstract MEF2D fusions are found in a special subtype of B-cell precursor acute lymphoblastic leukemia (BCP-ALL) with poor prognosis. In this study, we conducted high-throughput drug screenings using cell line and ex vivo cell model harboring, respectively, MEF2D::HNRNPUL1(MH) and MEF2D::BCL9(MB), the two major MEF2D fusions. We identified CUDC-907 as a highly potent dual-target inhibitor of PI3K/HDAC, demonstrating remarkable efficacy in inducing robust lethality while maintaining selectivity for MEF2D fusion-expressing cells. CUDC-907 effectively induced apoptosis and promoted the down-regulation of pre-BCR signaling. We discovered that the hyperactivation of the PI3K-AKT signaling pathway, HDAC9, and BCL2 contributed to the sustained state of MEF2D fusion (+) BCP-ALL. Importantly, CUDC-907 exerted dual regulatory function by targeting the integrative pathways of MEF2D fusions. It suppressed the PI3K-CREB pathway and fusion gene expression, while simultaneously inhibited transcriptional activity regulated by the MEF2D fusion-HDAC axis. CUDC-907 demonstrated remarkable efficacy in patient samples carrying distinct MEF2D fusion variants in vitro. Furthermore, this compound’s effectiveness and safety were confirmed in both MH/NRAS G12D BCP-ALL mouse model and MB patient-derived xenograft (PDX) model, outperforming conventional therapies. These results support the therapeutic potential of dual-pathway inhibition in MEF2D fusion (+) BCP-ALL and suggest CUDC-907 as a promising candidate for precision treatment in fusion-driven leukemias with similar molecular dependencies.